DESIGNING POTENTIAL DRUGS THAT CAN TARGET SARS-COV-2'S MAIN PROTEASE: A PROACTIVE DEEP TRANSFER LEARNING APPROACH USING LSTM ARCHITECTUR - Omar Dasser, PhD student; Moad Tahri, PhD student; Louay kila, MD; Abderrahim Sekkaki, PhD (Scholar Express Journals, 2022)
On December 2019, the world entered a state of alarm and dismay with the outbreak of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2) from Hubei-China and has infected as of the 1st October 2021 more than 233,770,079 people worldwide. This caused up to 4,782,608 deaths, and the World Health Organization (WHO) declared on January 2020 a global health emergency due to the rate at how much the infection is spreading and the mortality rate that approaches 4.5 percent [1]. It is considered to be extremely costly to bring a new drug to the market in terms of time and financial investment, which is, respectively, on average, around ten years and 1 billion dollars. Drug discovery alone can take up to 3 years which is a time we cannot accept in the context of a global pandemic
Keywords: considered; around; average; Drug